The Influence Of Leadership And Motivation On Employee Performance Moderated By Work Environment - Muhammad Anshar Jafar; Trimulato Trimulato; Ilham Gani (JPS (Jurnal Perbankan Syariah), 2023)
The study aims to show the effect of leadership and motivation on employee performance with the work environment as a moderating variable at the Niaga Madani Sharia Rural Bank (SRB) Makassar. The type of research used is quantitative with an associative approach and uses primary and secondary data. This study used a saturated sample of 52 respondents. The data analysis technique used moderated regression analysis (MRA), but before that, it was tested for validity, reliability, and classical assumptions with SPSS 26 software tools. The results showed that leadership significantly positively affected employee performance. Motivation does not affect employee performance. Work environment significantly positively affected employee performance. Leadership and motivation simultaneously influence employee performance. The work environment can significantly moderate the influence of leadership on employee performance. The work environment cannot moderate the effect of motivation on employee performance. This research can complement existing theory and be a reference for SRB in improving employee performance, especially in leadership.